A low-temperature lithium-ion battery negative electrode material and its preparation method and application

By using titanium niobate amorphous carbon coated graphite in the negative electrode material of lithium-ion battery and growing carbon nanotube cladding layer by atomization method, the problems of energy density reduction and safety hazards under low temperature conditions are solved, and high energy is achieved Improved density and safety.

CN118439602BActive Publication Date: 2024-12-27LIAONING ZHONGHONG ENERGY NEW MATERIAL CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202410526402.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-29
Publication Date
2024-12-27
Estimated Expiration
2044-04-29

AI Technical Summary

Technical Problem

Although the charging performance of existing lithium-ion battery anode materials has been improved under low temperature conditions, their energy density has been reduced and there are safety hazards, such as poor electronic conductivity and poor compatibility with electrolytes, resulting in safety problems.

Method used

Resin-based materials, niobium sources and titanium sources are mixed with graphite. After reaction and carbonization, amorphous carbon-coated graphite material is formed, and catalyst is deposited by atomization method to grow carbon nanotube clad layer to enhance electrons. Conductivity and compatibility reduce contact with electrolyte and reduce gas production.

Benefits of technology

It improves the energy density and low-temperature fast charging performance of the negative electrode material of lithium-ion battery, enhances the circulation performance and safety of the material, avoids gas production problems caused by direct contact between the core and the electrolyte, and improves electronic conductivity and first-time efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118439602B_ABST
    Figure CN118439602B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of battery material preparation, and discloses a low-temperature lithium-ion battery negative electrode material, a preparation method and application thereof. The preparation method of the low-temperature lithium-ion battery negative electrode material comprises the following steps: (1) mixing a resin-based material, hexadecyltrimethylammonium bromide, a niobium source, a titanium source, graphite and an organic solvent, and then reacting, drying and carbonizing them in sequence to obtain a titanium niobate amorphous carbon-coated graphite material; (2) atomizing and depositing the titanium niobate amorphous carbon-coated graphite material in sequence to obtain a titanium niobate carbon nanotube-coated graphite composite material, i.e., a low-temperature lithium-ion battery negative electrode material. The present invention coats titanium niobate carbon nanotubes on the graphite surface by a liquid phase method and a gas phase method, which improves the low temperature of the material while taking into account the energy density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery material preparation, and in particular to a low-temperature lithium-ion battery negative electrode material and a preparation method and application thereof. Background Art

[0002] As the market's requirements for the low-temperature performance of lithium-ion batteries increase, the negative electrode materials used in lithium-ion batteries are required to have excellent low-temperature charging capabilities under low-temperature conditions. At present, the negative electrode materials on the market are mainly artificial graphite and soft carbon or hard carbon coated on its surface to improve the low-temperature charging performance of the material. However, due to the slow diffusion coefficient of lithium ions under low-temperature conditions, the charging capacity is reduced, and at the same time, the cycle performance of the material is reduced under low-temperature conditions. Lithium titanate or lithium niobate is used as a negative electrode material in the fields of start-stop power supply due to its high lithium ion diffusion rate under low-temperature conditions, stable structure, large interlayer spacing, low expansion, and excellent cycle performance. However, its low energy density and poor high-temperature performance limit its wide application. For example, although coating lithium titanate or lithium niobate on the surface of graphite can improve the fast charging performance of the material, there is poor electronic conductivity and poor compatibility with the electrolyte, which is easy to produce gas and cause safety hazards. For example, patent application number CN201510390044.4 discloses a lithium titanate-coated graphite composite material and a preparation method thereof. Although the fast charging and low-temperature performance are improved, its energy density is reduced. Therefore, it is necessary to develop low-temperature negative electrode materials that need to improve low-temperature fast charging performance while taking into account the energy density of the material. Summary of the invention

[0003] In view of this, the purpose of the present invention is to provide a low-temperature lithium-ion battery negative electrode material and a preparation method and application thereof, so as to solve the problem that although the low-temperature performance of the existing low-temperature lithium-ion battery negative electrode material is improved, its energy density is reduced.

[0004] In order to achieve the above object, the present invention adopts the following technical solution:

[0005] The present invention provides a method for preparing a low-temperature lithium-ion battery negative electrode material, comprising the following steps:

[0006] (1) mixing a resin-based material, hexadecyltrimethylammonium bromide, a niobium source, a titanium source, graphite and an organic solvent, and then reacting, drying and carbonizing in sequence to obtain a titanium niobate amorphous carbon-coated graphite material;

[0007] (2) The titanium niobate amorphous carbon-coated graphite material is sequentially atomized and deposited to obtain a titanium niobate carbon nanotube-coated graphite composite material, i.e., a low-temperature lithium-ion battery negative electrode material.

[0008] Preferably, in step (1), the resin-based material includes phenolic resin, furfural resin or epoxy resin; the niobium source includes niobium chloride, niobium ethoxide, niobium oxalate or ammonium niobium oxalate; the titanium source includes titanium tetraisopropoxide, titanium sulfate, titanyl sulfate, titanium tetrafluoride, potassium titanium oxalate, titanium tetrachloride, titanium trichloride or butyl titanate; and the organic solvent includes ethylene glycol or isopropanol.

[0009] Preferably, in step (1), the mass fraction of the mixed solution consisting of the resin-based material and the organic solvent is 1-10%; the mass ratio of the total mass of the niobium source and the titanium source, the resin-based material, hexadecyltrimethylammonium bromide and the graphite is 1-5:5-20:1-10:100.

[0010] Preferably, in step (1), the reaction temperature is 30 to 150° C., the reaction time is 1 to 6 hours, and the drying is spray drying.

[0011] Preferably, in step (1), the carbonization temperature is 500-1000° C., and the carbonization time is 1-6 hours.

[0012] Preferably, in step (2), the atomization is to atomize and deposit the catalyst solution on the surface of the titanium niobate amorphous carbon-coated graphite material.

[0013] Preferably, the flow rate of the catalyst solution is 10 to 50 mL / min; in the catalyst solution, the catalyst includes ferric chloride, nickel chloride or cobalt chloride, and the solute includes acetone; the mass concentration of the catalyst solution is 8 to 12%; the atomization temperature is 100 to 200° C., the atomization pressure is 1 to 3 MPa, and the atomization time is 30 to 300 min.

[0014] Preferably, in the step (2), the gas used for deposition includes a heteroatom gas and a carbon source gas, the volume ratio of the heteroatom gas to the carbon source gas is 1 to 3:10, the heteroatom gas includes ammonia, sulfur dioxide, borohydride or phosphine, and the carbon source gas includes methane, ethane, ethylene, acetylene or propyne; the flow rate of the gas used for deposition is 100 to 500 mL / min; the deposition temperature is 600 to 1000° C., and the deposition time is 30 to 300 min.

[0015] The present invention also provides a low-temperature lithium-ion battery negative electrode material prepared by the method for preparing the low-temperature lithium-ion battery negative electrode material.

[0016] The present invention also provides application of the low-temperature lithium-ion battery negative electrode material in preparing a low-temperature lithium-ion battery.

[0017] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:

[0018] (1) A niobium source, a titanium source and a resin are mixed and coated on the graphite surface by a liquid phase method, and then carbonized to obtain titanium niobate and hard carbon coated graphite materials. The high specific capacity of titanium niobate (250 mAh / g) is utilized, which is higher than the specific capacity of lithium titanate (170 mAh / g). At the same time, the hard carbon formed after the carbonization of the doped resin improves the processing performance of the material and its compatibility with the electrolyte.

[0019] (2) Catalysts are deposited on the surface of titanium niobate amorphous carbon-coated graphite material by atomization, and carbon nanotubes are grown as a matrix to improve the electronic conductivity of the coating layer and its liquid retention performance. Compared with solid or liquid phase methods, the atomization method has the advantages of process controllability, high deposition efficiency, low agglomeration, and good consistency. At the same time, heteroatom-doped amorphous carbon is deposited on its outer layer by vapor deposition to improve the electronic conductivity and initial efficiency of the material, avoid direct contact between the inner core titanium niobate and the electrolyte, and reduce gas production. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0021] Figure 1 This is a SEM image of the titanium niobate carbon nanotube-coated graphite composite material prepared in Example 1. DETAILED DESCRIPTION

[0022] The present invention provides a method for preparing a low-temperature lithium-ion battery negative electrode material, comprising the following steps:

[0023] (1) mixing a resin-based material, hexadecyltrimethylammonium bromide, a niobium source, a titanium source, graphite and an organic solvent, and then reacting, drying and carbonizing in sequence to obtain a titanium niobate amorphous carbon-coated graphite material;

[0024] (2) The titanium niobate amorphous carbon-coated graphite material is sequentially atomized and deposited to obtain a titanium niobate carbon nanotube-coated graphite composite material, i.e., a low-temperature lithium-ion battery negative electrode material.

[0025] In step (1) of the present invention, the resin-based material includes phenolic resin, furfural resin or epoxy resin; the niobium source includes niobium chloride, niobium ethoxide, niobium oxalate or ammonium niobium oxalate; the titanium source includes titanium tetraisopropoxide, titanium sulfate, titanyl sulfate, titanium tetrafluoride, potassium titanium oxalate, titanium tetrachloride, titanium trichloride or butyl titanate; and the organic solvent includes ethylene glycol or isopropanol.

[0026] In step (1) of the present invention, the mass fraction of the mixed solution consisting of the resin-based material and the organic solvent is preferably 1-10%, more preferably 2-8%, and more preferably 5-7%; the mass ratio of the total mass of the niobium source and the titanium source, the resin-based material, the hexadecyltrimethylammonium bromide, and the graphite is preferably 1-5:5-20:1-10:100, more preferably 2-4:8-18:2-8:100, and more preferably 3:10-15:5-6:100.

[0027] In step (1) of the present invention, the reaction temperature is preferably 30-150°C, more preferably 40-120°C, and more preferably 50-100°C; the reaction time is preferably 1-6h, more preferably 2-5h, and more preferably 3-4h; and the drying is spray drying.

[0028] In step (1) of the present invention, the carbonization temperature is preferably 500-1000°C, more preferably 600-900°C, and more preferably 700-800°C; the carbonization time is preferably 1-6h, more preferably 2-5h, and more preferably 3-4h.

[0029] In step (2) of the present invention, atomization is to atomize and deposit the catalyst solution on the surface of the titanium niobate amorphous carbon-coated graphite material.

[0030] In the present invention, the flow rate of the catalyst solution is preferably 10 to 50 mL / min, more preferably 20 to 40 mL / min, and more preferably 30 to 35 mL / min; in the catalyst solution, the catalyst includes ferric chloride, nickel chloride or cobalt chloride, and the solute includes acetone; the mass concentration of the catalyst solution is preferably 8 to 12%, more preferably 9 to 11%, and more preferably 10%; the atomization temperature is preferably 100 to 200° C., more preferably 120 to 180° C., and more preferably 150 to 160° C.; the atomization pressure is preferably 1 to 3 MPa, more preferably 1.5 to 2.5 MPa, and more preferably 2 to 2.2 MPa; the atomization time is preferably 30 to 300 min, more preferably 50 to 250 min, and more preferably 100 to 200 min.

[0031] In step (2) of the present invention, the gas used for deposition includes a heteroatom gas and a carbon source gas, and the volume ratio of the heteroatom gas to the carbon source gas is preferably 1-3:10, more preferably 1.5-2.5:10, and more preferably 2-2.3:10; the heteroatom gas includes ammonia, sulfur dioxide, borohydride or phosphine; the carbon source gas includes methane, ethane, ethylene, acetylene or propyne; the flow rate of the gas used for deposition is preferably 100-500 mL / min, more preferably 200-400 mL / min, and more preferably 250-300 mL / min; the deposition temperature is preferably 600-1000°C, more preferably 700-900°C, and more preferably 800-850°C; the deposition time is preferably 30-300 min, more preferably 50-250 min, and more preferably 100-200 min.

[0032] The present invention also provides a low-temperature lithium-ion battery negative electrode material prepared by the method for preparing the low-temperature lithium-ion battery negative electrode material.

[0033] The present invention also provides application of the low-temperature lithium-ion battery negative electrode material in preparing a low-temperature lithium-ion battery.

[0034] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0035] Example 1

[0036] A method for preparing a low-temperature lithium-ion battery negative electrode material comprises the following steps:

[0037] (1) 10 g of phenolic resin was added to 200 g of ethylene glycol to prepare a 5 wt% solution, and then 5 g of hexadecyltrimethylammonium bromide was added and dispersed evenly to obtain a mixed solution, and then 1.35 g (0.005 mol) of niobium chloride and 1.42 g (0.005 mol) of titanium tetraisopropoxide were added and mixed evenly to obtain a coating solution, and then 100 g of graphite was added to the coating solution and mixed, reacted at a temperature of 100° C. for 3 h, spray dried, and then carbonized at a temperature of 800° C. for 3 h to obtain a titanium niobate amorphous carbon-coated graphite material;

[0038] (2) 100 g of titanium niobate amorphous carbon-coated graphite material was transferred to a tube furnace, and then 10 g of a 10% by mass ferric chloride acetone solution was deposited on the surface of the graphite material by atomization (temperature 150°C, pressure 2 MPa) at a flow rate of 30 ml / min for 120 min. The resulting material was then heated to 800°C, and ammonia and methane (ammonia: methane volume ratio = 2:10) were introduced at the same time. The flow rate of the mixed gas composed of ammonia and methane was 300 ml / min, and the deposition time was 120 min to obtain a titanium niobate carbon nanotube-coated graphite composite material, i.e., a low-temperature lithium-ion battery negative electrode material.

[0039] Example 2

[0040] A method for preparing a low-temperature lithium-ion battery negative electrode material comprises the following steps:

[0041] (1) 5 g of furfural resin is added to 500 g of ethylene glycol organic solvent to prepare a 1 wt% solution, and then 1 g of hexadecyltrimethylammonium bromide is added and dispersed evenly to obtain a mixed solution, and then 3.18 g (0.01 mol) of niobium ethoxide and 1.46 g (0.01 mol) of titanium sulfate are added and mixed evenly to obtain a coating solution, and then 100 g of graphite is added to the coating solution and mixed, reacted at a temperature of 30° C. for 6 h, spray dried, and then carbonized at a temperature of 500° C. for 6 h to obtain a titanium niobate amorphous carbon-coated graphite material;

[0042] (2) 100 g of titanium niobate amorphous carbon-coated graphite material was transferred to a tube furnace, and then 10 g of a 10% nickel chloride acetone solution was deposited on the surface of the graphite material by atomization (temperature 100°C, pressure 3Mpa) at a flow rate of 10 mL / min for 300 min; the resulting material was then heated to 600°C, and sulfur dioxide and acetylene (volume ratio of sulfur dioxide: acetylene = 1:10) were introduced at the same time, and the flow rate of the mixed gas composed of sulfur dioxide and acetylene was 100 mL / min, and the deposition time was 300 min to obtain a titanium niobate carbon nanotube-coated graphite composite material, i.e., a low-temperature lithium-ion battery negative electrode material.

[0043] Example 3

[0044] A method for preparing a low-temperature lithium-ion battery negative electrode material comprises the following steps:

[0045] (1) 20 g of epoxy resin was added to 200 g of isopropanol to prepare a 10 wt% solution, and then 10 g of hexadecyltrimethylammonium bromide was added and dispersed evenly to obtain a mixed solution, and then 2.69 g (0.005 mol) of niobium oxalate and 1.7 g (0.005 mol) of butyl titanate were added and mixed evenly to obtain a coating solution, and then 100 g of graphite was added to the coating solution and mixed, reacted at a temperature of 150° C. for 1 h, spray dried, and then carbonized at a temperature of 1000° C. for 1 h to obtain a titanium niobate amorphous carbon-coated graphite material;

[0046] (2) 100 g of titanium niobate amorphous carbon-coated graphite material was transferred to a tube furnace, and then 100 g of cobalt chloride acetone solution was deposited on the surface of the graphite material by atomization (temperature 200°C, pressure 1 MPa) at a flow rate of 50 mL / min for 30 min; the resulting material was then heated to 1000°C, and borohydride and ethylene (the volume ratio of borohydride:ethylene = 3:10) were introduced at the same time, and the flow rate of the mixed gas composed of borohydride and ethylene was 500 mL / min, and the deposition was carried out for 30 min to obtain a titanium niobate carbon nanotube-coated graphite composite material, i.e., a low-temperature lithium-ion battery negative electrode material.

[0047] Comparative Example 1

[0048] The difference from Example 1 is that niobium chloride and titanium tetraisopropoxide are not added, and the other parts are the same as Example 1.

[0049] Comparative Example 2

[0050] The difference from Example 1 is that no acetone solution of ferric chloride is added in step (2), and the rest is the same as Example 1.

[0051] The performance of the low-temperature lithium-ion battery negative electrode materials obtained in Examples 1 to 3 and Comparative Examples 1 to 2 was tested, and the test methods and results are as follows.

[0052] (1) SEM test:

[0053] The low temperature lithium ion battery negative electrode material prepared in Example 1 was subjected to SEM testing, and the results are as follows Figure 1 As shown. Figure 1 It can be seen that the low-temperature lithium-ion battery negative electrode material presents a secondary particle structure with a particle size between 10 and 15 μm.

[0054] (2) Physical and chemical properties test:

[0055] The powder resistivity, tap density, specific surface area, and diffusion coefficient of the low-temperature lithium-ion battery negative electrode materials obtained in Examples 1 to 3 and Comparative Examples 1 to 2 were tested according to the test method in the standard GB / T-24533-2019 "Graphite Negative Electrode Materials for Lithium-ion Batteries". The OI value of the powder material was tested by XRD. The test results are shown in Table 1.

[0056] Table 1 Physical and chemical properties of low temperature lithium ion battery negative electrode materials obtained in Examples 1 to 3 and Comparative Examples 1 to 2

[0057]

[0058]

[0059] It can be seen from Table 1 that the electrical conductivity of the low-temperature lithium-ion battery negative electrode materials obtained in Examples 1 to 3 is significantly higher than that in Comparative Example 1. The reason may be that the surface of the low-temperature lithium-ion battery negative electrode materials obtained in Examples 1 to 3 is coated with titanium niobate to improve the electronic conductivity of the material and carbon nanotubes are doped in the material to improve the electronic conductivity of the material, improve the diffusion coefficient and reduce the OI value.

[0060] (3) Button battery test:

[0061] The low-temperature lithium-ion battery negative electrode materials obtained in Examples 1 to 3 and Comparative Examples 1 to 2 were assembled into button batteries according to the following method:

[0062] The low-temperature lithium-ion battery negative electrode materials obtained in Examples 1 to 3 and Comparative Examples 1 to 2 were used as negative electrodes and assembled into button batteries with lithium sheets, electrolytes and diaphragms in a glove box with argon and water content less than 0.1 ppm. The diaphragm was celegard 2400; the electrolyte was a solution of LiPF6, in which the concentration of LiPF6 was 1 mol / L, and the solvent was a mixed solution of ethylene carbonate (EC) and diethyl carbonate (DMC) mixed in a mass ratio of 1:1.

[0063] The button cells were tested for their performance using a blue battery tester. The test conditions were: 0.1C rate charge and discharge, voltage range 0.005-2V, 3 cycles, then stopped, and then the discharge capacity under 1C was tested; at the same time, the specific capacity of 0.1 at low temperature -20°C was tested, and the low temperature capacity retention rate and cycle performance (25±3°C, 0.2C / 0.2C, 100 weeks) were calculated. The test results are shown in Table 2.

[0064] Table 2 Performance of button batteries obtained from low-temperature lithium-ion battery negative electrode materials obtained from Examples 1 to 3 and Comparative Examples 1 to 2

[0065]

[0066] It can be seen from Table 2 that the button-type battery made of the low-temperature lithium-ion battery negative electrode material obtained in Examples 1 to 3 has a significantly higher discharge capacity and efficiency than the button-type battery made of the low-temperature lithium-ion battery negative electrode material obtained in Comparative Examples 1 to 2. The experimental results show that the graphite composite material of the present invention can make the battery have good discharge capacity and efficiency; the reason is that the surface coating of titanium niobate and its carbon nanotubes in the graphite improves the electronic and ionic conductivity of the material, and titanium niobate has the characteristic of high first efficiency, thereby improving the first efficiency of the composite material.

[0067] (4) Soft pack battery performance test:

[0068] The low temperature lithium ion battery negative electrode material obtained in Examples 1 to 3 and Comparative Examples 1 to 2 is used as the negative electrode active material, and the positive electrode active material ternary material (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2), electrolyte and diaphragm are assembled into 5Ah soft pack batteries. The diaphragm is celegard 2400, and the electrolyte is LiPF6 solution (the solvent is a mixed solution of EC and DEC with a volume ratio of 1:1, and the concentration of LiPF6 is 1.3mol / L). The prepared soft pack batteries are marked as A-2, B-2, C-2, D-2, and E-2, and the cycle and rate performance of the batteries are tested. The test results are detailed in Table 3.

[0069] 1) Cycle performance: The cycle performance of the battery is tested at a charge and discharge rate of 0.2C / 0.2C and a voltage range of 2.8 to 4.2V at a temperature of -20±3°C;

[0070] 2) Rate performance: Charge the battery to 100% SOC at a rate of 2C using constant current + constant voltage mode, and then calculate the constant current ratio = constant current capacity / (constant current capacity + constant voltage capacity).

[0071] Table 3 Performance of soft-pack batteries obtained from low-temperature lithium-ion battery negative electrode materials obtained from Examples 1 to 3 and Comparative Examples 1 to 2

[0072]

[0073]

[0074] It can be seen from Table 3 that the cycle performance of the soft-pack batteries prepared using the low-temperature lithium-ion battery negative electrode materials obtained in Examples 1 to 3 is significantly higher than that of the soft-pack batteries prepared using the low-temperature lithium-ion battery negative electrode materials obtained in Comparative Examples 1 to 2. The reason is that the surface of the low-temperature lithium-ion battery negative electrode materials obtained in Examples 1 to 3 is coated with titanium niobate to reduce the consumption of lithium ions during charging and discharging and has high liquid retention performance, thereby improving its cycle performance; at the same time, carbon nanotubes are doped in the low-temperature lithium-ion battery negative electrode materials obtained in Examples 1 to 3 to improve the electronic conductivity of the material and improve the rate performance.

[0075] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a low-temperature lithium-ion battery negative electrode material, characterized in that: The steps include: (1) mixing a resin-based material, hexadecyltrimethylammonium bromide, a niobium source, a titanium source, graphite and an organic solvent, and then reacting, drying and carbonizing in sequence to obtain a titanium niobate amorphous carbon-coated graphite material; (2) sequentially atomizing and depositing the titanium niobate amorphous carbon-coated graphite material to obtain a titanium niobate carbon nanotube-coated graphite composite material, i.e., a low-temperature lithium-ion battery negative electrode material; In the step (1), the resin-based material includes phenolic resin, furfural resin or epoxy resin; the niobium source includes niobium chloride, niobium ethoxide, niobium oxalate or ammonium niobium oxalate; the titanium source includes titanium tetraisopropoxide, titanium sulfate, titanyl sulfate, titanium tetrafluoride, potassium titanium oxalate, titanium tetrachloride, titanium trichloride or butyl titanate; and the organic solvent includes ethylene glycol or isopropanol; In the step (2), the gas used for deposition includes a heteroatom gas and a carbon source gas, and the volume ratio of the heteroatom gas to the carbon source gas is 1 to 3:10; In the step (2), the atomization is to atomize and deposit the catalyst solution on the surface of the titanium niobate amorphous carbon-coated graphite material.

2. The method for preparing a low-temperature lithium-ion battery negative electrode material according to claim 1, characterized in that: In the step (1), the mass fraction of the mixed solution composed of the resin-based material and the organic solvent is 1-10%; the mass ratio of the total mass of the niobium source and the titanium source, the resin-based material, hexadecyltrimethylammonium bromide, and the graphite is 1-5:5-20:1-10:

100.

3. The method for preparing the low-temperature lithium-ion battery negative electrode material according to claim 1, characterized in that: In the step (1), the reaction temperature is 30 to 150° C., the reaction time is 1 to 6 hours, and the drying is spray drying.

4. The method for preparing a low-temperature lithium-ion battery negative electrode material according to claim 1, characterized in that: In the step (1), the carbonization temperature is 500 to 1000° C., and the carbonization time is 1 to 6 hours.

5. The method for preparing the low-temperature lithium-ion battery negative electrode material according to claim 1, characterized in that: The flow rate of the catalyst solution is 10 to 50 mL / min; in the catalyst solution, the catalyst includes ferric chloride, nickel chloride or cobalt chloride, and the solute includes acetone; the mass concentration of the catalyst solution is 8 to 12%; the atomization temperature is 100 to 200° C., the atomization pressure is 1 to 3 MPa, and the atomization time is 30 to 300 min.

6. The method for preparing the low-temperature lithium-ion battery negative electrode material according to claim 1, characterized in that: In the step (2), the heteroatom gas includes ammonia, sulfur dioxide, borohydride or phosphine, and the carbon source gas includes methane, ethane, ethylene, acetylene or propyne; the flow rate of the gas used for deposition is 100 to 500 mL / min; the deposition temperature is 600 to 1000° C., and the deposition time is 30 to 300 min.

7. A low-temperature lithium-ion battery negative electrode material prepared by the method for preparing a low-temperature lithium-ion battery negative electrode material according to any one of claims 1 to 6.

8. Use of the low-temperature lithium-ion battery negative electrode material according to claim 7 in the preparation of a low-temperature lithium-ion battery.

Citation Information

Cited By

  • Nitrogen-doped carbon-coated titanium niobate negative electrode material as well as preparation method and application thereof

    CN121011645A